2008
DOI: 10.1785/0120080093
|View full text |Cite
|
Sign up to set email alerts
|

Seismic-Wave Propagation in Alluvial Basins and Influence of Site-City Interaction

Abstract: The geometrical and mechanical features of alluvial deposits have a major influence on seismic wave propagation and amplification. However, for alluvial basins located in densely urbanized areas, the surface structures such as buildings could influence seismic wave propagation near the free surface. In this paper, the influence of surface structures on seismic wave propagation is analyzed numerically in the case of an actual 2D shallow basin. At a local scale, the vibration of a surface structure can induce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
10
45
0
Order By: Relevance
“…Despite different physical origins, the observations made in the resonant X-direction (double-peak resonance, antiresonance trough, modified phase) recall those described in dynamics when two co-resonant mass-spring systems are associated (Hartog 1956). Numerical simulations, reported by Wirgin & Bard (1996), Clouteau & Aubry (2001), Semblat et al (2008) and Groby & Wirgin (2008) have shown similar splits of the layer resonance when adding resonant structures at the top surface of an elastic layer. However, comparisons are not straightforward due to different sets of configurations, hypotheses and frequency ranges in the models.…”
Section: Site-city Interactionsupporting
confidence: 53%
“…Despite different physical origins, the observations made in the resonant X-direction (double-peak resonance, antiresonance trough, modified phase) recall those described in dynamics when two co-resonant mass-spring systems are associated (Hartog 1956). Numerical simulations, reported by Wirgin & Bard (1996), Clouteau & Aubry (2001), Semblat et al (2008) and Groby & Wirgin (2008) have shown similar splits of the layer resonance when adding resonant structures at the top surface of an elastic layer. However, comparisons are not straightforward due to different sets of configurations, hypotheses and frequency ranges in the models.…”
Section: Site-city Interactionsupporting
confidence: 53%
“…This result is consistent with the findings of Mucciarelli et al (2008) andDitommaso et al (2009), who noticed that, although the soil-structure interaction in inhabitated areas might act in general as a dampener for the recorded wavefield (Semblat et al, 2008), there is a shift of energy that concentrates at frequencies close to the frequencies of the buildings yielding to local peaks of amplification in the Fourier spectrum.…”
Section: Building-soil Interactionsupporting
confidence: 92%
“…The inertial soil-structure interaction effect on the freefield ground motion is also known for a long time (Jennings 1970;Kanamori et al 1991). However, the site-city interaction effects, which significantly modify the free-field ground motion in basins, became a critical issue only after the 1985 Mexico earthquake (Wirgin and Bard 1996;Guéguen et al 2002;Kham et al 2006;Semblat et al 2008). Very large reduction of spectral amplification at double resonance (37.10 %) at the top of B8 building in regular homogeneous city 2 at its natural frequency (1.15 Hz) as compared to the single B8 building in the same basin was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In SCI, both the kinematic and inertial interactions play their roles, but it is very difficult to separate out the individual effect during an earthquake excitation. Kham et al (2006) and Semblat et al (2008) reported that the SCI under double-resonance condition can lead to a significant variation of seismic wave field as compared to the free-field motion and concluded that the effects of SCI are beneficial in some parts of the city and detrimental in the other parts of the basin. The SCI effects on the ground motion strongly depend on the urban configuration mainly on the city heterogeneity and city density.…”
mentioning
confidence: 99%